The Effect of Advertising Exposure and Reference Group Toward Purchase Intention - Pamungkas, Adie (KINERJA, 2024)
Advertising is still a powerful promotional medium today, where most aspects of the economy have shifted online. In this digital era, conventional advertising, namely television advertising, is still an option and is still effective for business people to use in promoting their products or brand campaigns. Apart from that, suggestions or recommendations from people around you can have an influence on someone when they make a decision to buy or consume a product. These two factors are combined and researched to find out their influence on purchasing interest from potential consumers. The population in this research are residents of the city of Tasikmalaya and the sampling method is judgment to select respondents to be studied. After the research was carried out, the results were found to show that there were both simultaneous and partial influences from the advertising exposure and reference group variables on the purchase interest variable